Differences in motoric and anthropometric space between 12-year old boy basketball players and students - Pireva, F.; Vehapi, S.; Mikic, B.; Pireva, A.; Gashi, E.; Kelmendi, D. (Sport Science - International Scientific Journal of Kinesiology, 2015)
The study included a total of 113, 12-year old male students. 55 students were regular students in grade 6 of lower secondary school, while 58 were of the same age but they attend regular exercises at basketball school. The sample was treated with 7 anthropometric variables, 4 basic motoric tests, and 6 situational motoric basketball tests. The purpose was to confirm relations and to determine what is the effect of active involvement of these students in regular workouts at the basketball school on differences in development of anthropometric features as well as basic kinaesthetic skills and situational skills in basketball game.